PERCEIVED USEFULNESS, BIMA MOBILE QUALITY, AND THEIR IMPACT ON SATISFACTION AND REUSE INTENTIONS AMONG GEN Z - Nurhalisa Fadjrin; Rosita Mei Damayanti; Laras Safira (Jurnal Ilmu Ekonomi dan Pembangunan, 2025)
This study investigates the impact of Perceived Usefulness (PU), Service Quality (SERVQUAL), and Customer Satisfaction on Reuse Intention of mobile banking applications among Generation Z users at Bank Jateng. Using the Technology Acceptance Model (TAM) and SERVQUAL framework, the research explores how these factors influence customer satisfaction and their intention to continue using mobile banking services. Data was collected from 190 respondents through a structured questionnaire and analyzed using descriptive and inferential statistics via STATA. The findings show that customer satisfaction mediates the relationship between service quality and reuse intention. Service quality has a significant effect on reuse intention, particularly through its impact on satisfaction, while Perceived Usefulness shows an indirect effect. The study suggests that banks focus on improving both functional features and user experience to enhance customer retention.